Opportunities And Challenges Of Mainstreaming Religious Moderation At Public College In Indonesia - Ramadhan, Mochammad Rizal (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
This research aims to discuss the opportunities and challenges of mainstreaming religious moderation in public universities in Indonesia. This research uses a qualitative approach, and data processing uses descriptive-analytical methods. The results and discussion of this research show that there are several opportunities and challenges in efforts to mainstream religious moderation in public universities in Indonesia, especially on the island of Java, which has varied diversity. Public universities are a model of true Indonesia, meaning that diversity in religion has been created within them, so it is necessary to mainstream religious moderation so that relations between community members, both internal and external, can be well maintained. It is also hoped that the creation of a mutualistic symbiosis between religious communities can be pursued and maintained to strengthen the meaning of diversity. An important effort in mainstreaming religious moderation in public universities is to apply the values of religious moderation in a comprehensive, systematic and constructive manner.